Configurações urbanas, fatores socioeconômicos e conforto térmico em São José do Rio Preto, SP - Menegaldo, Vanize (Universidade Federal de São Carlos, 2022)
Urban settings and socioeconomic factors possibly related to an urban thermal comfort condition. This work seeks to investigate the relationship between environmental comfort and urban environmental settings in the city of São José do Rio Preto. The was developed through the analysis of four urban areas, two in areas of methodology and two areas by constructive pattern, and two elevations of special social interest. Based on the definition of the four representative urban areas, campaigns were carried out to collect data on temperature and air humidity simultaneously with the collection of reports from passers-by on perception and satisfaction with the thermal environment. The information was adjusted and converted into the Physiological Equivalent Temperature Index - PET, adopting it as a parameter of thermal comfort. In this way, it was possible to evaluate based on the characteristics of each area, such as environmental and relational comfort conditions with the socioeconomic factors that were formed. The green results point to the need for greater attention to public areas, especially in less privileged areas of infrastructure, in order to obtain the most urban and thermally balanced urban areas. However, the socioeconomic factor was not predominant in relation to the other constructive factors, such as the H/W ratio, FVC, permeability and the distribution of green areas.
Urban settings, socioeconomic factors and thermal comfort in São José do Rio Preto, SP
Keywords: Clima urbano; Análise microclimática; Morfologia urbana; Relações socioespaciais; PET; Urban climate; Microclimatic analysis; Urban morphology; Socio-spatial relations; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::METEOROLOGIA::CLIMATOLOGIA; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ASPECTOS FISICO-AMBIENTAIS DO PLANEJAMENTO URBANO E REGIONAL